Prospective observational study on caudal epidural block for transurethral resection of prostate in patients with comorbidities - Paudel, Bandana; Paudel, Sumitra; Das, Chitta Ranjan (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: The most important goal of anaesthesia for geriatric patients with comorbid diseases is to maintain normal homoeostasis of different systems during and after surgery. This prospective study was conducted to evaluate the success rate and associated complications of the caudal epidural block for transurethral resection of prostate in elderly patients with comorbid diseases. Methods: This is a prospective study of a cohort of 100 elderly patients posted for transurethral resection of prostate with comorbid diseases belonging to American Society of anaesthesiologists physical status II, III and IV over a period of 1 year from April 2015 to April 2016. Standard recommended technique for caudal epidural block was followed. Time of onset, spread, duration of analgesia, intensity of block, complications, and unwanted effects were noted. Results: The mean age was 73.5+-7.69. Eighty-two percent patients belonged to ASA III and IV grade. The majority (87%) had excellent to a good quality of anaesthesia with no motor block. 83% of patients had the onset of analgesia between 5-15 minutes and 78% had a duration between 90-130 minutes. Three patients had patchy analgesia and they were considered as a failure. No death was encountered in the study. Conclusion: Caudal epidural block is a safe, effective anaesthetic technique for transurethral resection of the prostate in elderly with comorbid diseases of other systems.